A low‐profile wideband dual‐polarization patch antenna with antisymmetric feeding network. Issue 10 (27th June 2019) - Yang, Yintang; Zhang, Jianqiang; Lan, Haokun; Liu, Maliang
Abstract: In this paper, a novel broadband dual‐polarization patch antenna is proposed. Antisymmetric Γ feeding network is applied to excite the radiating patch etched on the upper side of the horizontal substrate, which could minimize the undesired radiation from the probe and extend the impedance bandwidth. For verifying the proposed approach, a prototype is fabricated and measured, the simulated and measured results show the antenna has a wide impedance bandwidth of 48% (1.66‐2.71 GHz) for S11 < −10 dB, as well as stable radiation gain around 9.5 dBi with low cross‐polarization. In addition, the total height of the antenna is only 0.17 λ 0 ( λ 0 is the free space wavelength of central frequency) and high port‐to‐port isolation is better than 30 dB. The characteristics of the proposed antenna illustrate it can be an indication for a micro base station in the mobile communication system.